Restricted Concave Kite Five-Body Problem - A. R. Kashif; M. Shoaib (Advances in Astronomy)
The restricted concave kite five-body problem is a problem in which four positive masses, called the primaries, rotate in the concave kite configuration with a mass at the center of the triangle formed by three of the primaries. The fifth body has negligible mass and does not influence the motion of the four primaries. It is assumed that the fifth mass is in the same plane of the primaries and that the masses of the primaries are m1, m2, m3, and m4, respectively. Three different types of concave kite configurations are considered based on the masses of the primaries. In case I, one pair of primaries has equal masses; in case II, two pairs of primaries have equal masses; in case III, three of the primaries have equal masses. For all three cases, the regions of central configuration are obtained using both analytical and numerical techniques. The existence and uniqueness of equilibrium positions of the infinitesimal mass are investigated in the gravitational field of the four primaries. It is numerically confirmed that none of the equilibrium points are linearly stable. The Jacobian constant C is used to investigate the regions of possible motion of the infinitesimal mass.